Prevalence of Malocclusion among School Children of Biratnagar, Nepal (Orthodontic Journal of Nepal, 2021)
Introduction: Various forms of malocclusion are a matter of serious concern in Nepalese population. This study was carried out to understand the prevalence of malocclusion among the school children of Biratnagar. The objective of this research is to find out the prevalence of malocclusion of children from different schools of Biratnagar visiting the Pedodontics and Orthodontics department of Nobel Medical College and Teaching Hospital, Biratnagar.Materials and Method: A descriptive cross sectional study method was used in this research. Data was collected by using direct observation of the subjects and occlusal assessment was done according to Angle’s classification and Dewey’s modification types of class I, class II and class III malocclusion.Result: Subjects with normal occlusion was found to be 39 % and with malocclusion was found to be 61%. Among them, class I malocclusion (60%) and angles class II div I subjects (88.33%) were in majority of the total study population.Conclusion: The present study helps to determine the prevalence of malocclusion and need of orthodontic treatment for the school children of Biratnagar